Laparoscopic Management of Uncomplicated Intestinal Malrotation in Children (Bangladesh Journal of Endosurgery, 2014)
Introduction: Anomalies of midgut rotation and fixation associated with volvulus  and vascular compromise require urgent surgical intervention. Recent literature  supports laparoscopic management of intestinal malrotation in children. But  conversion and complication rates of laparoscopic treatment are higher, especially  in neonates, and when associated volvulus and bowel ischemia are present. The  authors present their experience and results of laparoscopic management of  uncomplicated cases of intestinal malrotation in children excluding newborns.Methods: A retrospective analysis of all the children who underwent elective laparoscopic  Ladds (LL) procedure was done. All neonates and children presenting  with signs of acute volvulus and bowel ischemia were excluded from LL procedure.  Between April 2007 and April 2013, 12 patients underwent LL procedure at the  authors institution. Of the 12 patients, 8 were boys and the age ranged from  3 months to 9 years. All patients were presented with symptoms of abdominal pain  and intermittent bilious vomiting. Diagnosis of intestinal malrotation was suggested  either by Doppler ultrasonography or upper gastrointestinal contrast study and  confirmed by diagnostic laparoscopy in all the patients. A standard Ladds procedure  with appendectomy was performed laparoscopically in all cases.Results: All  procedures were completed laparoscopically. Average duration of procedure was  about 95 min (75130 min). Feeding was started on post-op day 1 and all patients  were discharged by day 4. There were no immediate or early postoperative complications,  but one patient developed intestinal obstruction on follow-up and required  intervention. All patients are doing well on latest follow-up.Conclusion: LL procedure  can be successfully performed in infants and children with uncomplicated  cases of intestinal malrotation. Conversion rates are negligible and complications  are minimal if strict selection criteria are followed.DOI: http://dx.doi.org/10.11593/bje.2013.0103.0017Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 1-5